Accounting Theory and Cost Accounting. - Benninger, L. J. (The Accounting Review, 1965)
Abstract Although cost accounting became fully absorbed into the formal accounts, it has nevertheless retained over the years something of its original and esoteric nature. Data incorporated into the cost accounts receive a transforming action sometimes not clearly encompassed in guidelines set forth for the practice of financial accounting. Thus, there arises a dilemma of both description and theory formulation. Cost accounting, when well developed, represents a highly specialized segment of the accounts. At the same time, however, its data become an important aspect of many problems facing the general accountant. Broadly speaking, what apparently is needed in accounting theory formulation is a study leading to a comprehensive and unified statement concerning accounting theory as a whole. Such a statement should integrate a presentation of purposes, a coherent general theory rationale, and guiding standards, which would apply to the broad outlines of the accounts. Theory expressions made in this statement must be capable of extension to all accounting processes. Finally, as regards the subject of this article, steps need to be taken to extend accounting theory formulation to specific problems encountered in the area of cost accounting.